Integration of Environmental Degradation Issues in Biodiversity Learning in the Primary School Teacher Education Program at Iskandar Muda University - Cut Maulina; Nena Puspita Sari; Ruslaini Ruslaini; Muzakkir Zakaria; Fakhri Ramadhan (JIPI (Jurnal IPA & Pembelajaran IPA), 2026)
The increasing rate of environmental degradation requires the education sector to play a more active role in fostering ecological awareness among younger generations. However, in higher education particularly in the basic science concepts course environmental degradation issues are often not optimally integrated into the learning process, resulting in prospective teachers’ understanding remaining largely conceptual and less contextual. This study aims to analyze the integration of environmental degradation issues into biodiversity learning in the Primary School Teacher Education Program (PGSD) at Iskandar Muda University and to examine its impact on prospective teachers’ conceptual understanding and ecological awareness. The research employed a qualitative approach using a case study design. Data were collected through classroom observations, in-depth interviews with lecturers and prospective teachers, and analysis of instructional documents such as the semester learning plan and teaching materials. The findings reveal that integrating environmental degradation issues into biodiversity learning enhances prospective teachers’ conceptual understanding, strengthens their analytical abilities regarding environmental problems, and fosters greater ecological awareness. Learning that connects scientific concepts with real environmental conditions was found to create a more contextual and meaningful learning experience. The study highlights the importance of developing environment-based pedagogical strategies in teacher education. Therefore, it is recommended that environmental issues be systematically integrated into teacher education curricula to support sustainability-oriented education